Magnetised and sulfide functionalised zinc oxide nanocomposite for dispersive micro-solid-phase extraction of lead (II) and cadmium (II) in water samples. Issue 5 (9th April 2023) - Tadese, Miresa; Amde, Meseret; Leta Danno, Bayissa; Benti, Lemessa; Megersa, Negussie
ABSTRACT: In this study, a dispersive micro-solid-phase extraction (D-µ-SPE) technique was developed prior to flame atomic absorption spectrometric analysis of trace amounts of lead and cadmium in waters. For this purpose, a magnetized and sulphide functionalised zinc oxide nanocomposite (Fe3 O4 /ZnO@S NC) was effectively synthesised through sol-gel and sono-chemical methods. The surface phenomena, size, shape, elemental composition as well as electromagnetic interactions of the synthesised nanomaterials were characterised by Fourier transform infrared spectroscopy, X-ray-diffraction, transmission electron microscopy, scanning electron microscopy-energy dispersive X-ray spectrometry, and ultraviolet-visible spectroscopy. Experimental parameters that can affect the adsorption and desorption of the metal ions such as pH, adsorbent dose, sample volume, eluent type, concentration and volume, shaking time and speed, and ionic strength were optimised. Under the optimum conditions, preconcentration factor of 48.2 for Pb(II) and 51.5 for Cd(II), limit of detection of 1.1 µg/L for Pb(II) and 0.4 µg/L for Cd(II), and >80% recovery values were obtained. The precision of the D-µ-SPE method was also evaluated by calculating the inter- and intra-day relative standard deviation of seven replicate measurements and <10% were obtained. Finally, the developed D-µ-SPE method was successfully applied for the determinations of lead and cadmium in different real-world water samples. Therefore, the D-µ-SPE is simple, fast and sensitive and hence, highly recommended for the enrichment of metal ions from various types of waters.